Peran Media Sosial dalam Katekese guna Membangun Iman di Era Digital - Margareta Vera Lema; Intansakti Pius X (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
This article discusses the role of social media in catechesis to build faith in the digital age. The digital age has brought about major changes in the way we communicate and access information. Social media, as a product of the digital technology revolution, has become a highly efficient and effective means of communication, connecting individuals around the world quickly and easily. The Catholic Church views social media as an important tool for evangelization, faith formation, and spreading the values of love and truth. Through social media, the Church can influence more people to take the message of Christ to different corners of the world and offer new opportunities for catechesis to reach out to people and nurture their faith. Digital catechesis is a very effective tool in educating and deepening the faith of the people, creating a lively and dynamic atmosphere of faith. The church has an important role in guiding its people to integrate their faith in digital life, making technology a tool to strengthen faith and Christian values. This article provides some suggestions for the effective use of social media in catechesis, such as the development of innovative catechesis programs, digital education for parishioners, collaboration with communities and technologists, and evaluation of the impact of social media use. In this strategy, the Church can utilize social media to strengthen the faith of the people and create a more faithful and dignified community in the digital age.